Productivity effects of dengue in Brazil - Sonia R. Bhalotra; Gabriel Facchini; Aline Menezes; Rudi Rocha (University of Essex, Institute for Social and Economic Research (ISER), 2019)
Although understanding the role of health in driving labor market outcomes is a matter of great importance, it has proven difficult to isolate this effect due to empirical challenges and a lack of compelling sources of identification. We obtain causal estimates of the effect of health on income and welfare dependency through two different channels: a negative health shock (dengue outbreak) and a positive health shock (opening of a health-care facility). To do this, we rely on instrumental variables and difference-in-difference methods, as well as on novel datasets. We find that dengue outbreaks lower the average working hours and income. This effect is particularly high for low-income individuals, but conditional cash transfer programs can insulate them from this shock. On the other hand, the opening of a new health-care facility in a families catchment area rises family per capita income and employment. All together, this evidence suggest that health shocks are an important part of income, poverty and welfare dependency.
Keywords: 330